Packaging and storage of partially-dried coconut meat - Padilla, Jennifer E.
A study was made to determine the effectivity of partial drying and packing on coconut meat as a partial treatment to lengthen its shelf-life. The study involved three phases wherein Phase 1 determined the optimum moisture content, partial drying time and the best packaging material for coconut meats. The optimum moisture content was found to be 15% with an optimum partial drying time of 5 1/2 to 6 hours. It lasted for three days when packed in cheesecloth. Phase 2 is the determination of the sorption properties of both treated and untreated coconut meat samples. The shape of the sorption isotherm curves is slightly sigmoid or S-shaped. It was also found out that the untreated meat was more hygroscopic than the treated meat. Phase 3 is the critical moisture content (CMC) determination wherein the optimized samples were exposed to 100% relative humidity at 38°C. The shelf-life was determined to be only two days. A high initial peroxide value and % free fatty acid content, 17.96 meq/kg and 1.12% respectively, were obtained. The CMC was 9.92%.